Home in the Poetry of Saudi Arabia Poets: Abdus-Salam Hafeth an Example of a Distinguished Arab (7) - Yahya Saleh Hasan Dahami (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
A poet's ‘homeland’ is the place he associates with his humanity, such as his aspirations, pain, and incantation. The focus of this study is on the Saudi poet, Abdus-Salam Hashem Hafeth, and the concept of home as he depicts it in his poem 'Nostalgia, Oh My Home'. The paper consistently makes an effort to illuminate some literary traits of current Saudi poetry, the theme of national affection, and its connection to classical Arabic. This investigation aims to elucidate some literary facets of contemporary poetry in the Kingdom of Saudi Arabia. The issue of ‘homeland’ is given particular attention in the study as a sign of the route that contemporary Saudi poetry is taking. There is a case to be made that Saudi poetry is currently flourishing among Arab writers, critics, and poets. The researcher wants to emphasize the poet's knowledge while also emphasizing his dedication to his vast country, the Kingdom of Saudi Arabia, by using the poet's wonderful city of Al-Madinah Al Monawarah as a symbol. The researcher, on the other hand, makes an attempt to look at how the poet utilizes the Arabic language in his poem. This study uses the critical-analytical method in assessing Hafeth's poem, 'Nostalgia, Oh My Home,' concentrating on the image of homeland as its major theme as well as the aptitude of the poet in masterfully employing the Arabic language. The result of the study shows the importance of the concept of homeland in the poetry of Saudi Arabia and the greatness of the Arabic poetic language as a beacon of illumination. By employing the poet's lovely city – Al-Madinah - as a metaphor for his love of his infinite homeland, the Kingdom of Saudi Arabia, he also hopes to demonstrate the poet's brilliance and ingenuity. After a brief introduction, the study turns to an outline of Saudi poetry and then a concise introduction of the poet Abdus-Salam Hafeth. The study then applies a critical-analytical method to analyze a few lyrical lines from the poem ‘Nostalgia, Oh My Home’, placing a focus on the idea of home as its main theme. The study's succinct conclusion is followed by a few recommendations.